Prospects for growth : a biblical view of population, resources, and the future - Beisner, E. Calvin (WIPF AND STOCK, 2019)
The warnings are loud and clear: the world is dangerously overpopulated; natural resources are becoming scarce; catastrophic manmade global warming could lead to the death of our planet. Are these accurate predictions we ignore at our own peril, or are they politically motivated scare tactics designed to promote a radical agenda? In this important book, respected author E. Calvin Beisner brings biblical principles of theology, anthropology, and ethics to bear on these crucial questions. What do the Scriptures say about population, freedom/civil government, natural resources, and management of the environment? Is man meant to be servant, master, or steward of the earth? This compelling study will help everyone concerned about the future of the earth make informed decisions on strategic issues of our day.